Pengaruh Konsentrasi AB Mix dan Frekuensi Semprot Pupuk Organik Cair (POC) terhadap Pertumbuhan Tanaman Pakcoy (Brassica rapa L.) pada Hidroponik Sistem Deep Floating Technique (DFT) - KRISNA, I MADE AGUS; WIJANA, GEDE; DARMAWATI, IDA AYU PUTRI (Agrotrop : Journal on Agriculture Science; Vol 13 No 1 (2023), 2023)
Effect of AB Mix Concentration and Frequency of Liquid Organic Fertilizer Spray (POC) on the Growth of Pakcoy ( Brassica rapa L.) Plants in the Deep Floating Technique (DFT) Hydroponic System. Pakcoy ( Brassica rapa L.) is one of the vegetables that can be cultivated using a hydroponic system. Deep Floating Technique (DFT) hydroponic system is one of the hydroponic techniques in vegetable cultivation by using pools in installations and circulation with slow flow. The nutrients used in hydroponic cultivation are generally AB mix nutrients, but the use of liquid organic fertilizer ( pupuk organik cair /POC) in hydroponic vegetable cultivation needs more attention to suppress the use of inorganic fertilizers. The study aims to determine the response of pakcoy growth to the addition of POC and to obtain the concentration of AB mix and the frequency of POC spray which gives the best pakcoy plant growth. This research was carried out from January to March 2021 in a green house with a UV plastic roof in Banjar Gentong, Tegallalang District, Gianyar Regency, Bali. Geographically, it is located at 8°48'38 south latitude and 115°28'04 east longitude at an altitude of 510-550 meters above sea level. The study used a Nested Randomized Block Design where the POC spraying frequency was nested at the concentration of AB mix. The data obtained from the variables were analyzed statistically using analysis of variance (ANOVA) according to the design that was carried out. If the treatment has a significant effect, then the BNT test at the 5% level will be carried out. The addition of POC spraying frequency on pakcoy showed a significant effect, the highest yield ware shown in the addition of POC spraying frequency once every 2 days at all concentration treatment levels. The combination of giving AB mix 1,000 ppm with the POC spraying frequency every 2 days (K3F1) gave the best growth for pakcoy.